Upaya Meningkatkan Kompetensi Pedagogik Guru Dalam Manajemen Kelas Melalui Supervisi Administrasi Kelas Di SMP Negeri 1 Simpang Teritip Kabupaten Bangka Barat Tahun Pelajaran 2022/2023 - Purwestri Madya H (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Indicators of improving the quality of education, in this case are the components of school principals and teachers, because in their hands school policy and management as well as the process of teaching and learning activities can be carried out well, synergy between school principals and teachers which is vertically instructive, a symbiotic mutualism, as well as communication and mutual complementing is an ideal condition for creating a good teaching and learning activity process. Indicators of improving the quality of education, in this case are the principal and teacher components, because in their hands the school policy and management as well as the teaching and learning activity process can be carried out well, the synergy between the school principal and teachers is Vertical instructiveness, symbiotic mutualism, as well as communication and complementarity are the ideal conditions for creating a good teaching and learning process. The problem that arises is whether through Class Administration Supervision can Teachers Improve Pedagogical Competence in Class Management at SMP Negeri 1 Simpang Teritip West Bangka Regency for the 2022/2023 Academic Year? The aim of this research is to improve teachers' pedagogical competence in classroom management through supervision of classroom administration at SMP Negeri 1 Simpang Teritip, West Bangka Regency, Academic Year 2022/2023. The number of pages in PTS is 31 pages. The results of the research showed that the results of the pre-cycle, cycle I, cycle II, the teacher's ability to manage and manage the class experienced an increase in percentage at each stage, from the new pre-cycle it reached 67% (fair), in the first cycle it reached 68% (good), and the first cycle II 88% (very good). Based on the results of the research above, it can be concluded that through academic supervision classes can improve Teacher Pedagogical Competence in Class Management at SMP Negeri 1 Simpang Teritip.